2007
DOI: 10.1097/01.iae.0000231544.43093.40
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Displacement of Submacular Hemorrhage

Abstract: The results of pneumatic displacement of submacular hemorrhage using perfluoropropane gas are encouraging, thus questioning the role of tPA in the management of such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Ohji et al reported that when a subretinal hemorrhage is relatively fresh, only injection of gas can remove it from the subfoveal space [8]. However, Gopalakrishan et al reported that pneumatic displacement without tPA may not be worthwhile in eyes with a submacular hemorrhage, due to wet AMD [22]. More recently, the addition of intravitreal bevacizumab to the injection of tPA and gas is reported to be safe, and superior to the displacement of submacular hemorrhage alone with tPA and gas [23,24].…”
Section: Discussionmentioning
confidence: 96%
“…Ohji et al reported that when a subretinal hemorrhage is relatively fresh, only injection of gas can remove it from the subfoveal space [8]. However, Gopalakrishan et al reported that pneumatic displacement without tPA may not be worthwhile in eyes with a submacular hemorrhage, due to wet AMD [22]. More recently, the addition of intravitreal bevacizumab to the injection of tPA and gas is reported to be safe, and superior to the displacement of submacular hemorrhage alone with tPA and gas [23,24].…”
Section: Discussionmentioning
confidence: 96%
“…Gopalakrishan et al ,[4] have reported a series of 20 cases of SMH who were treated with pneumatic displacement out of which five had AMD. In these patients they concluded that pneumatic displacement without TPA had poor results.…”
Section: Discussionmentioning
confidence: 99%
“…In three studies, only intravitreal gas injection was used in an attempt to displace the hemorrhage [21,22,23]. Four studies employed either gas injection or both rtPA and gas injected intravitreally, depending on the study arm [24,25,26,27].…”
Section: Resultsmentioning
confidence: 99%